The future of work and play: From automated vehicles to working from home - Kun, Andrew L.; Shaer, Orit; Sadun, Raffaella; Boyle, Linda Ng; Lee, John D. (2020)
ABSTRACT How can technology support workers in our rapidly changing world? How can we help them be productive and creating, and how can we support their overall wellbeing? Our team explores these broad questions for two specific areas: working in future automated vehicles, and working from home. We argue that making progress in these areas will require convergent research - the type of research in which experts from multiple backgrounds create new languages of expression and new approaches that integrate disciplines. In this document we present our own steps towards such a convergent research approach to the future of work and play. Keywords work from home, automated vehicles, convergent research ABOUT THE AUTHOR/S Andrew L. Kun University of New Hampshire andrew.kun@unh.edu Orit Shaer Wellesley College oshaer@wellesley.edu Raffaella Sadun Harvard Business School rsadun@hbs.edu Linda Ng Boyle University of Washington linda@uw.edu John D. Lee University of Wisconsin - Madison John.d.lee@wisc.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).